Sport facility and event management - Aicher, Thomas; Paule-Koba, Amanda L.; Newland, Brianna L. (Jones & Bartlett Learning, 2016)
Sport Facility and Event Management focuses on the major components of both facility and even management: planning, financing, marketing, implementation, and evaluation. It integrates timely theoretical foundations with real world practicality and application to provide the reader with a strong foundation in facility and event management